Comprehensive and Comparative Analysis of HDI, WPI, CPI and CCI on Stock Market Returns (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The stock market returns reflects the performance of the economy and the expectations from the market. In developing markets like India, stock market performance is not only dependent on the performance of the firms but also on the economic and social indicators. This paper aims to analyse the compounded and relative effects of the Human Development Index (HDI), Consumer Price Index (CPI), Wholesale Price Index (WPI), and Consumer Confidence Index (CCI) on stock market returns in India between the years 2015 and 2025. The analysis is based on 128 monthly observations of each Bombay Stock Exchange (BSE) and the National Stock Exchange (NSE) with the help of descriptive statistics, Correlation, Augmented Dickey-Fuller (ADF) unit root tests, multiple regression (OLS), and Autoregressive Distributed Lag (ARDL) models. The correlation between BSE and NSE is nearly 1 (r = 0.999), confirming that the indices move in near-perfect tandem. There is an exceedingly high correlation (r = 0.9999) between CPI and HDI, confirming near-perfect multi-collinearity. Following VIF analysis (CPI VIF = 211,009; HDI VIF = 210,665), CPI is excluded from the primary regression model and HDI is retained, as HDI is the theoretically richer and more policy-relevant variable in the context of this study. The revised model (BSE/NSE ~ CCI + WPI + HDI) resolves the extreme multi-collinearity while maintaining R² = 0.9769 (BSE) and R² = 0.9705 (NSE). All three retained predictors are significant at p < 0.001. CCI is negatively correlated with BSE (–0.652) and NSE (–0.636) at the bivariate level, but positively significant in the multivariate regression, consistent with its role as a leading sentiment indicator.Monthly HDI data was sourced from the UNDP Human Development Data Centre (hdr.undp.org). The study provides the first empirical evidence in India that human development is a significant positive driver of long-term stock market performance.Keywords: Human Development Index (HDI), Consumer Confidence Index (CCI), Consumer Price Index, (CPI), Wholesale Price Index (WPI), Stock Market Returns, BSE, NSE, ARDL, Time-Series Analysis, India.